Cliff ecosystems: A critical yet uncharted frontier for research and conservation - Martí March-Salas; María Begoña García; Isaac H. Lichter-Marck; Juan Lorite; Manuel J. Steinbauer (Basic and Applied Ecology)
Cliffs, all over the world, are often exceptionally rich in endemic, rare and endangered plant species. Historically, cliffs have been among the least human-disturbed habitats, but they now face increasing direct and indirect pressures. Human activities, such as recreational rock climbing, can lead to habitat deterioration or species loss, while the ongoing climate warming can also alter the characteristics of cliff habitats and their inhabitants. Despite their outstanding conservation value and the growing pressures they face, there is relatively little research on cliff ecosystems. Here, we aim to contextualize previous research and showcase contributions from this Special Issue entitled “Ecology, Evolution and Conservation of Cliff Flora”. Articles in this issue address a great variety of perspectives in cliff research such as: evaluating the potential loss of unique genetic diversity in endangered and rare cliff plants; understanding past, present and future distribution patterns, population dynamics, and evolutionary processes in cliffs in the context of climate change; examining abiotic and biotic feedbacks and interactions occurring in these habitats; assessing the current conservation status of cliff flora at global scale, and exploring new pathways to study and monitor the diversity of cliff habitats. Our goal was to present a variety of examples of past and current research, highlight gaps, novel approaches, and future directions for basic and applied cliff ecology. In this context, we aim to help elucidate evolutionary and functional patterns and processes in this unique ecosystem, while also promoting the conservation of cliff habitats and their hosted organisms.